Studi Minat Membaca Siswa Melalui Cerita Lucu di SMP Negeri 18 Baubau - Nety Nety; Riza Rizky Taharuddin (English Education Journal, 2021)
The problem statement based on the background of the research, the research of problems statement formulated, is there any significant difference Study of Students in Reading Interest through Humor Story at SMP Negeri 18 Baubau. This research used a quantitative approach with applying Descriptive methods. Population on this research was the eighth grade students of SMP Negeri 18 Baubau consisted of 256 students. The sample was taken by using a purposive sampling technique consisted of 30 students. The results of this research showed that the based on T table the value was 1,991 and T count was 62,129. It can conclude that t count was 62,129 > 1,991 of T table, so that Ho was rejected and H1 was accepted. It means that there was not significant difference Study of students’ interest in reading through humor story.